2009
DOI: 10.3390/toxins1020188
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of an In-House Reference Material Containing Fumonisins in Thai Rice and Matrix Extension of the Analytical Method for Japanese Rice

Abstract: Mycotoxin contamination in rice is less reported, compared to that in wheat or maize, however, some Fusarium fungi occasionally infect rice in the paddy field. Fumonisins are mycotoxins mainly produced by Fusarium verticillioides, which often ruins maize. Rice adherent fungus Gibberella fujikuroi is taxonomically near to F. verticillioides, and there are sporadic reports of fumonisin contamination in rice from Asia, Europe and the United States. Therefore, there exists the potential risk of fumonisin contamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Fumonisins B 1 , B 2 and B 3 (FB 1 , FB 2 and FB 3 ) were determined in rice by the method of Oh et al (2009) , with some modifications. A 10 g sample plus 1 g NaCl was submerged in 50 ml water for 30 min ( Kushiro et al 2008 ; Awaludin et al 2009 ) and extraction was completed by blending (Polytron) for 3 min with 50 ml acetonitrile-methanol (1 + 1, v/v). After centrifuging at 2000 rpm for 10 min and filtering (Whatman #1), 40 ml PBS (pH 7) were added to a 10 ml aliquot of extract.…”
Section: Methodsmentioning
confidence: 99%
“…Fumonisins B 1 , B 2 and B 3 (FB 1 , FB 2 and FB 3 ) were determined in rice by the method of Oh et al (2009) , with some modifications. A 10 g sample plus 1 g NaCl was submerged in 50 ml water for 30 min ( Kushiro et al 2008 ; Awaludin et al 2009 ) and extraction was completed by blending (Polytron) for 3 min with 50 ml acetonitrile-methanol (1 + 1, v/v). After centrifuging at 2000 rpm for 10 min and filtering (Whatman #1), 40 ml PBS (pH 7) were added to a 10 ml aliquot of extract.…”
Section: Methodsmentioning
confidence: 99%
“…HorRat values were 0.8 to 1.4. Pre-column derivatisation with OPA was also used in two reports examining extraction and clean-up procedures for isolating fumonisins from masa flour (De Girolamo et al, 2011a) or rice (Awaludin et al, 2009). The first of these examined extraction from yellow, white, and blue masa flours, comparing acidic extraction with the use of EDTA (De Girolamo et al, 2011a).…”
Section: Fumonisinsmentioning
confidence: 99%
“…In examining masa flour and tortilla chips the authors found combined (FB 1 +FB 2 ) levels of up to 1,800 µg/kg in masa flour and 960 µg/kg in tortilla chips. Awaludin et al (2009) developed an in-house reference material and used it to examine factors affecting the extraction of fumonisins from rice. Several solvent:sample ratios were examined.…”
Section: Fumonisinsmentioning
confidence: 99%
See 1 more Smart Citation